Rhetorical Strategies of Cherokee Women in Petitions Against Cultural Erasures - Poudel, Prativa (Gipan, 2025)
The article explores how Cherokee women used strategic language, adapting some specific terminology and cultural ideas from Euro-American tradition in the petitions to convince them back. This article aims to analyze how they strategically used white (Euro- American) cultural element in the petition to fight for their rights and resist the easure of their culture. The main focus here is on examining the three Cherokee women's petitions from 1817, 1818, and 1831, written under the leadership of Nancy Ward (Ghigua). The petitions are analyzed on the basis of metaphors related to paternalism and maternalism, the appropriation of “civilization” discourse, and the conceptualization of land as both a physical and spiritual inheritance, placing all of these idea within a postcolonial feminist theoretical framework that centers Indigenous women's agency and resistance. The growing threat to sovereignty also led to a shift in their tone, terms, and expression. The findings reveal the nuanced ways in which Cherokee women leveraged the dominant culture's language to resist cultural erasure and assert their rights. The Cherokee women's petitions are an important archival artifact to show the political ability as well as the accurate and significant history of Cherokee women. Finally, this article supports the hypothesis that the tactical adjustment of Euro-American cultural elements in their petitions was key to Cherokee women's advocacy efforts to negotiate spiritual beliefs.